Ultrasonication and RSM-based optimization of antioxidant activity, saccharide composition and fatty acids from Phoenix dactylifera L. Medjool date seeds influenced by ethanol - Thirubuvanesvari-Duraivelu, Pushpa; Abd Gani, Siti Salwa; Hassan, Masriana; Halmi, Mohd Izuan Effendi; Abutayeh, Reem Fawaz; Al-Najjar, Mohammad A.A.; Abu-Odeh, Ala’ (African Journals Online (AJOL), 2024)
In response with the demand in date industry finding on sustainable solution for date seeds management and its bioactive rich constituent, current study envisaged the optimum condition for the ultrasound extraction of Phoenix dactylifera L. Medjool date seeds and its antioxidative activity by employing a three-level three-factor Box–Behnken design via response surface methodology (RSM). Ethanol (EtOH) concentration (50-80%), time (30-90 min) and temperature (40-70 °C) were the independent variables investigated for ABTS•+ scavenging antioxidant activity and subjected to analysis of variance (ANOVA). The optimum conditions for maximum antioxidant activity (60.93% ± 0.021) were achieved at 80% EtOH, 44 min and at 57 °C, where the effect of EtOH concentration were notably significant. The observed agreement between the experimental (60.93% ± 0.021) and predicted (60.35%) values indicated the employed model suitability while substantiates the successful implementation of RSM for optimizing extraction parameters. The optimized extract characterized through UPLC-QTOF/MS and GC-MS/MS, detailed the presence of saccharides (isomaltose, mannotriose and stachyose) and volatile compounds, namely 5 saturated fatty acids that encompassed within the 8.42% (w/w) of total fat obtained. This verifies the ability of the solvent mixture extracting fatty acids and saccharides even under high EtOH concentration.